THE INFLUENCE OF MOTOR ABILITIES ON KICKING KARATE TECHNIQUE - Ivica Šćepanović; Aleksandar Vlahović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2013)
The general aim of this study was to determine the existence of influence of motor abilities on performance of mae-geri kicking technique in younger karate practitioners. Number of 39 male subjects, aged 15 years ± 6 months, from 4 karate clubs situated in Podgorica and Nikšić, participated in this study. Assessment of basic motor abilities (18 variables) and specific motor abilities (1 variable) was performed using standardized tests. Regression analysis was used to determine the relation between basic motor abilities and the criteria. Inspection of the results shows that the predictor system has a statistically significant influence on the executing speed of mae-geri karate technique (R=.91; R2=.84; Q=.00). Flamingo (β=.36; Q-β=.04), hand tapping (β=.35; Q-β=.02), 20m shuttle run (β=.58; Q-β=.00), push-ups on parallel bars (β=.36; Q-β=.04) and endurance on high bar (β=-.57; Q-β=.00) are the individual variables that showed a statistically significant effect on the criteria.